2014
DOI: 10.4049/jimmunol.1301373
|View full text |Cite
|
Sign up to set email alerts
|

CD4+ T Cells Contain Early Extrapulmonary Tuberculosis (TB) Dissemination and Rapid TB Progression and Sustain Multieffector Functions of CD8+ T and CD3− Lymphocytes: Mechanisms of CD4+ T Cell Immunity

Abstract: The possibility that CD4+ T cells can act as “innate-like” cells to contain very-early M. tuberculosis (Mtb) dissemination and function as master helpers to sustain multiple effector functions of CD8+ T cells and CD3-negative lymphocytes during development of adaptive immunity against primary tuberculosis(TB) has not been demonstrated. We showed that pulmonary Mtb infection of CD4-depleted macaques surprisingly led to very-early extrathoracic Mtb dissemination, whereas CD4 deficiency clearly resulted in rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
74
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 76 publications
4
74
2
1
Order By: Relevance
“…HIV infection induced CD4 T-cell depletion, and mice or nonhuman primates experimentally depleted of CD4 T cells are highly susceptible to Mtb infection (Müller et al 1987;Orme 1988;Leveton et al 1989;Flory et al 1992;Lin et al 2012;Pawlowski et al 2012;Yao et al 2014). Indeed, it is well established that T helper cells are critical for containment of Mtb.…”
Section: Priming Of Mtb-specific T-cell Responsesmentioning
confidence: 99%
“…HIV infection induced CD4 T-cell depletion, and mice or nonhuman primates experimentally depleted of CD4 T cells are highly susceptible to Mtb infection (Müller et al 1987;Orme 1988;Leveton et al 1989;Flory et al 1992;Lin et al 2012;Pawlowski et al 2012;Yao et al 2014). Indeed, it is well established that T helper cells are critical for containment of Mtb.…”
Section: Priming Of Mtb-specific T-cell Responsesmentioning
confidence: 99%
“…In vivo studies in a non-human primate model demonstrated that 19 CD4+ T cells were required to sustain multiple CD8+ T cell and CD3+ lymphocyte 20 effector functions and to prevent rapid TB progression during M.tb infection. CD8 T 21 cells also play a major role in anti-tuberculosis immunity [22,23]. However, the differences in antigen-specific T cells in subjects with different M.tb infection statuses 1 in humans are not clear.…”
Section: The Distributions and Functions Of T Cell Subsets At The Tubmentioning
confidence: 99%
“…However, the differences in antigen-specific T cells in subjects with different M.tb infection statuses 1 in humans are not clear. Most studies have focused on differences between active 2 tuberculosis and healthy individuals [23][24][25]. Studies on the distribution of T cell 3 subsets in populations with different M.tb infection statuses were limited [26][27][28].…”
Section: The Distributions and Functions Of T Cell Subsets At The Tubmentioning
confidence: 99%
“…Previous studies, using adoptive transfer of immune CD4 ϩ T cells (21,22), specific in vivo antibody depletion of CD4 ϩ T cells in mice (23)(24)(25) or macaques (26,27), and effects of CD4 ϩ T cell depletion due to infection with HIV (28), demonstrate the crucial role of antigen-specific CD4 ϩ T cells in the control of M. tuberculosis infection. Furthermore, a T helper 1 (Th1)-type response and the production of interferon gamma (IFN-␥) have been linked to favorable outcomes of M. tuberculosis infection in animal models and humans (29)(30)(31).…”
mentioning
confidence: 97%